Pengaruh Estetika Desain terhadap Persepsi Merek dan Keputusan Pembelian Konsumen di Pasar Internasional - Rizky Fiqran Pratama (Design Journal, 2025)
The study aimed to examine the importance of product design aesthetics in influencing consumer brand perception and brand purchasing behavior in a culturally diverse market. Using a mixed methods approach, the researchers obtained quantitative data through questionnaires distributed to 300 respondents selected through stratified random sampling from three leading economies (USA n=100, Germany n=100, Japan n=100). Multivariate regression analysis showed a significant positive effect of aesthetics on brand equity formation (β=0.71, p<0.001; R²=0.42), explaining up to 42% of the variance in purchase intention. The results showed significant cultural differences in design preferences: 73% of Western consumers (USA: 75%, Germany: 71%) favored more minimalist designs, with monochrome & geometric trends; while 68% of Japanese respondents favored polychromic arrangements with detailed symbolic components. Rather than a uniform global product design paradigm, these findings suggest a flexible conceptual framework of the Cultural Design Adaptation Matrix (CDAM). The CDAM paradigm systematizes assets into four strategic dimensions: color semiotics, form-language localization, symbolic value alignment, and tactile experience customization and it is known that multinational companies can increase market penetration by 18-22% by modifying culture-specific design elements, while the theoretical contributions expand our knowledge of aesthetic cognition in cross-cultural consumer behavior.